Student’s acceptance of e-learning during the COVID-19 pandemic - Nur Farha Shaafi; Zulinda Ayu Zulkipli; Nur Ainaa Najiha Mohd Azam; Mohammad Mubarrak Mohd Yusof (Institute of Advanced Engineering and Science, 2023)
Electronic learning (e-learning) has become the main method of teaching and learning for many educational institutions during the COVID-19 pandemic. The purpose of this study is to investigate the students’ acceptance of e-learning during the COVID-19 pandemic. Quantitative research methods were utilized in order to obtain the necessary data. A total of 100 respondents from three science courses, which were Biology (ED247), Chemistry (ED260), and Physics (ED248) in the Faculty of Education, University Teknologi MARA, Puncak Alam answered a questionnaire given via Google Forms. The IBM SPSS version 25.0 software was used for data analysis. The results show that the students’ acceptance towards e-learning is low based on research question 1 (mean=3.05, SD=.796), research question 2 (mean=1.18, SD=.386), research question 3 (mean=1.18, SD=.435) and research question 4 (mean=1.44, SD=.608). In conclusion, the student’s acceptance of e-learning during the COVID-19 pandemic is significant to improve an educational process by creating and sustaining meaningful learning.